The first European family with gastric adenocarcinoma and proximal polyposis of the stomach: case report and review of the literature - Repák, Rudolf; Kohoutová, Darina; Podhola, Miroslav; Rejchrt, Stanislav; Minárik, Marek; Mináriková, Lucie; Lesko, Michal; Bures, Jan (Gastrointestinal endoscopy, 2016)
BACKGROUND AND AIMS: Gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS) has to date been recognized in only 8 families worldwide. Recently, different point mutations within the Ying Yang 1 (YY1) binding motif in promoter 1B of the APC gene were assigned as causal in 6 families with GAPPS. METHODS: We diagnosed GAPPS across 3 generations in a Czech white family. RESULTS: The proband's mother died of gastric cancer at 49 years of age. The proband died of gastric cancer at 56 years of age. All 3 of the proband's daughters inherited polyposis, involving exclusively the gastric fundus and body, with relative sparing of the lesser curve. The daughters have all been regularly surveyed endoscopically. Polyposis progressed rapidly with intestinal differentiated low-grade and high-grade dysplasia present on polypectomy specimens 5 years after the original diagnosis. On this basis, all 3 of the proband's daughters were scheduled for prophylactic total gastrectomy. Unfortunately, the middle daughter presented with generalized gastric adenocarcinoma and died at the age of 26 years. The other 2 daughters (aged 30 and 23 years) underwent total gastrectomy within 6 weeks of their sister's death; histology of surgical specimens showed gastric adenocarcinoma stage IA (pT1a, N0, M0) in both cases. Bi-directional Sanger sequencing of promoter 1B revealed a point mutation (c.-191 T>C) in all 3 daughters of the proband. CONCLUSIONS: Atypical endoscopic progression of the fundic gland polyposis, with the presence of dysplasia on polypectomy specimens and genetic testing with recently discovered mutations in promoter 1B of the APC gene might help clinicians to decide whether prophylactic gastrectomy should be performed.
Keywords: mutace; dospělí; gastroskopie; Female; polypy; Gastrectomy; Pedigree; Adult; mladý dospělý; ženské pohlaví; rodokmen; lidé; geny APC; Gastroscopy; Mutation; Stomach Neoplasms; adenomové polypy; gastrektomie; Adenocarcinoma; Polyps; Male; Genes, APC; nádory žaludku; adenokarcinom; Adenomatous Polyps; Young Adult; lidé středního věku; promotorové oblasti (genetika); mužské pohlaví; Promoter Regions, Genetic; Middle Aged; Humans